Dynamic investigation of triangles inscribed in a circle, which tend to an equilateral triangle. Issue 1 (2nd January 2017) - Stupel, Moshe; Oxman, Victor; Sigler, Avi
ABSTRACT: We present a geometrical investigation of the process of creating an infinite sequence of triangles inscribed in a circle, whose areas, perimeters and lengths of radii of the inscribed circles tend to a limit in a monotonous manner. First, using geometrical software, we investigate four theorems that represent interesting geometrical properties, after which we present formal proofs that rest on a combination between different fields of mathematics: trigonometry, algebra and geometry, and the use of the concept of standard deviation that is taken from statistics.